2020
DOI: 10.1017/s0033291720003062
|View full text |Cite
|
Sign up to set email alerts
|

Depressed mood and anxiety as risk factors for hypertensive disorders of pregnancy: a systematic review and meta-analysis

Abstract: Background Psychosocial factors have been implicated as both a cause and consequence of hypertension in the general population but are less understood in relation to hypertensive disorders of pregnancy (HDP). The aims of this review were to (1) synthesize the existing literature examining associations between depression and/or anxiety in pregnancy and HDP and (2) assess if depression and/or anxiety in early pregnancy was a risk factor for HDP. Methods A comprehensive search of Medline, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 89 publications
(110 reference statements)
0
23
1
Order By: Relevance
“…Such over-adjustments can degrade precision and/or open biasing pathways that distort the estimated association [ 35 , 47 ]. Given emerging research on the bi-directional relationship between HDP and depression [ 48 , 49 ] and established research on the impact of maternal mental health on toddler development [ 50 ], we included maternal depression covariates in our analysis expecting it to positively confound (prenatal depression) or lie on the causal pathway (postpartum depression) between HDP and child development. Importantly, maternal mental health has not been integrated into previous studies addressing this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Such over-adjustments can degrade precision and/or open biasing pathways that distort the estimated association [ 35 , 47 ]. Given emerging research on the bi-directional relationship between HDP and depression [ 48 , 49 ] and established research on the impact of maternal mental health on toddler development [ 50 ], we included maternal depression covariates in our analysis expecting it to positively confound (prenatal depression) or lie on the causal pathway (postpartum depression) between HDP and child development. Importantly, maternal mental health has not been integrated into previous studies addressing this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Although depression and anxiety are common among pregnant women, leading to postpartum depression and/or anxiety and other mental health problems, combining these conditions with HDP is especially detrimental to maternal and infant health. A meta-analysis of 61.2 million pregnancies suggested that depression and anxiety were clinically associated with HDP [11]. Specifically, this study reported that women who met the clinical cut-off score for depression and/or anxiety symptoms had a 39% increased relative risk of HDP diagnosis than those without these conditions [11].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 61.2 million pregnancies suggested that depression and anxiety were clinically associated with HDP [11]. Specifically, this study reported that women who met the clinical cut-off score for depression and/or anxiety symptoms had a 39% increased relative risk of HDP diagnosis than those without these conditions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Women with perinatal depression are more likely to engage in risky health behaviors such as poor nutrition, substance use, or limited attendance at prenatal care ( Klawetter et al, 2020 ). Perinatal depression was also linked to a variety of poor pregnancy outcomes, including gestational diabetes ( Lee et al., 2020 ), hypertensive disorders ( Shay et al., 2020 ), preterm birth, and low birth weight ( Jarde et al, 2016 ). After birth, women affected by perinatal mood and anxiety disorders were at risk for postpartum depression ( Aris-Meijer et al., 2019 ; Grigoriadis et al., 2018 ), anxiety ( Aris-Meijer et al., 2019 ), psychosis, and suicide ( Van Niel & Payne, 2020 ).…”
Section: Introductionmentioning
confidence: 99%